Sistem Monitoring Kehadiran Siswa Oleh Orang Tua Berbasis Sms Gateway - Fitrian Bilontalo; Sitti Suhada; Nikmasari Pakaya (Diffusion: Journal of Systems and Information Technology, 2021)
SMKN 1 Suwawa is one of the vocational hight schools which locates in Bone Bolango District with the total number of students is 480. In one day observation at the school, there Were many students who did truant during the class hour. The action has been frequently an issue between teachers and parents. Student's parents found out that their children have been Actively engaged in the theaching and learning process. That is what they expect while the students did the country. The research is aimed at facilitating the school to inform the  Parents regarding the absence of their children in the class. Student's absence is a form of indicipline action to be decreased at school. System development applies the prototype Method through the PHP programming language and MySQL database. The research finding Revealed that SMS gateway based monitoring system by parents on student attendance is Addressed to facilitate the school to inform student's parents related to student attendance.  The system displays data of student attendance both in each class and as a whole.